Numbers of Mute Swans Cygnus olor in Great Britain: results of the national census in 2002 - Ward, Robin M; Cranswick, Peter A; Kershaw, Melanie; Austin, Graham E; Brown, Allan W; Brown, Lyndesay M; Coleman, Jon C; Chisholm, Helen C; Spray, Chris J (Wildfowl, 2013)
In 2002, a census of Mute Swans Cygnus olor was carried out in Great Britain and the Isle of Man, to determine the size of the Mute Swan population during the breeding season and to distinguish between the numbers of breeding and non-breeding birds. Coverage of the whole country had been attempted previously, in 1955/56, 1978, 1983 and 1990, but was deemed impractical for this census. Instead, coverage of randomly selected 10-km squares was undertaken, which reduced the amount of fieldwork required and made it possible to calculate confidence intervals for the estimated population size. The population size was estimated at 31,700 birds, with 95% confidence levels of 28,600–35,200 birds. Separate estimates were made of the breeding or territorial component (6,150 pairs, with 95% confidence levels of 5,550–6,740 pairs) and non-breeding component (19,400 unpaired non-breeding individuals, 95% confidence levels of 16,700–22,200 birds). The Mute Swan population in Britain and the Isle of Man has thus increased by 23% over the period 1990–2002, a slower rate than during the 1980s. Coverage was achieved for all but 96 (92%) of the 1,100 10-km squares originally selected for surveying, a major improvement on previous censuses. This high level of coverage contributed to the accuracy of the population size estimate in 2002.